Menghadapi Keterbatasan Modal dan Jaringan Pemasaran : Strategi Guna Pemberdayaan pada UMKM Pengrajin Alumunium - Dhea Natali; Poppy Indriani (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
The results of the Thematic Real Work Lecture held in Tanjung Atap Barat Village, Tanjung Batu District, Ogan Ilir Regency, during the odd semester of the 2024/2025 academic year are presented in this report. The main focus of the research was to find and solve the capital and marketing network problems faced by MSME aluminum craftsmen. The research found that capital and marketing issues are major obstacles to the growth of MSMEs. The research was conducted through an interdisciplinary approach. The individual socialization method was used in this research to provide an understanding of digital marketing strategies that can increase product visibility without spending a lot of money. The results show that aluminum craftsmen can improve the competitiveness of their products and expand their marketing network by utilizing online platforms and social media.